Trends in overweight and obesity prevalence in Tuscan schoolchildren (2002–2012). Issue 17 (29th May 2015) - Lazzeri, Giacomo; Panatto, Donatella; Pammolli, Andrea; Azzolini, Elena; Simi, Rita; Meoni, Veronica; Giacchi, Mariano V; Amicizia, Daniela; Gasparini, Roberto
Abstract: Objective: The aim of the present study was to examine the prevalence and time trends in childhood overweight including obesity and obesity among Tuscan children from 2002 to 2012. Design: Cross-sectional study at five time points (Tuscan Nutritional Surveillance Surveys conducted in the years of 2002, 2006, 2008, 2010 and 2012). Trained personnel directly measured the height and weight of the subjects. BMI was assessed by means of the International Obesity Task Force (IOTF) and WHO cut-offs. Setting: Representative sample of children in the Tuscany region (Italy). Subjects: Children ( n 7183) aged between 7·5 and 9·5 years (3711 boys and 3472 girls). Results: With respect to the estimation of the absolute prevalence level of childhood overweight, a discrepancy was observed between the two criteria. In all surveys, more boys than girls were overweight (including obesity). Trend analysis showed a significant decrease in the prevalence of overweight including obesity and obesity in Tuscan children from 2002 to 2012 (32·0 % v . 25·8 %, P <0·001 on using IOTF criteria and 37·7 % v . 34·3 %, P <0·001 on using WHO criteria for overweight including obesity; and 10·0 % v . 6·7 %, P <0·001 on using IOTF criteria and 12·5 % v . 11·3 %, P =0·035 on using WHO criteria for obesity). Conclusions: The present study is the first report from an Italian region showing a significant decrease in childhood obesity and overweight in the last 10 years. This reduction is probably a result of regional and local actions that have taken place in many sectors of society. However, efforts should be made to lower the prevalence of childhood obesity and overweight further.